METODE DAN TIORI ILMIAH DALAM FILSAFAT ILMU - Aiyub Jamaluddin, Aiyub Jamaluddin; Syamsul Rijal, Syamsul Rijal (Yayasan Darul Hasanah Aceh, 2025)
Philosophy of science is an activity of thinking, comprehensive, radical and deep and functional in the development of scientific methods and theories. Where the philosophy of science is seen as science, namely an assumption such as how to think, how empirical results are achieved, and where the limitations are. Meanwhile, the scientific method consists of a series of activities in the form of: introducing and formulating problems, collecting relevant information, formulating hypotheses, carrying out experiments and publishing or disseminating information. Then a scientific theory or scientific theory is a collection of propositions that include certain concepts that are interconnected or related logically to provide an explanation of a number of events or phenomena. The condition of interconnectedness between these concepts presents a complete and systematic view of the phenomenon or scientific object being studied so that it is able to explain and predict the phenomenon or scientific object in question. In principle, the ultimate goal of science is to produce theories, namely in the form of explanations of natural phenomena. So that this research results in the philosophy of science and scientific methods complementing and expanding knowledge, giving rise to disciplined understanding in scientific work, as well as increasing motivation as researchers to carry out their research using good scientific methods.